Contrasting Monetary Regimes in Africa - Honohan, Patrick (IMF Working Papers; Working Paper ;, 1997)
In post-independence sub-Saharan Africa, institutional arrangements for monetary policy have taken a variety of forms, although the historical evolution of many African financial systems has been similar. This paper identifies five different regimes and examines how they evolved over time. It focuses on how the alternative institutional arrangements have influenced the performance of monetary policy under fiscal pressure, and concludes that, although the trend appears to be toward more flexible regimes, the transition to greater flexibility can exacerbate problems of credibility and of macroeconomic management.